Thymos and Paideia: On what i most certain in the past and expected in the future - Fobel, Pavel; Fobelová, Daniela (Folia Philosophica, 2001)
The considerations presented in the paper concentrate on two notions from the ancient Greek philosophy: thymos and paideia which, even at present, turn out to be very influential. We live in an overtechnicised society which, for human sake, has developed the most complicated of technologies. It cannot be thus surprising that those achievements have exerted a deep influence on the lives of people. Man has "really” become, or is becoming, the master of nature. In the attitude to benefits there disappears the usefulness of the theoretical knowledge resulting from self-evaluation, from reflection on oneself and on the spiritual reasons for action. Such a way of thinking does not belong to the usefully needed sphere. What is forgotten are such important matters as the mutual “enrichment” of one culture through another. We do not remember about the distinguished personages of this or that culture or a historical period. This problem has been in the philosophical-politological work of Francis Fukayama in the essays "The End of History?" and the "Last Man" in which, among others, he introduces the notion of "recognition” derived from Plato’s thymos in which he grasped its ethical dimension and which he accepted in its primary meaning, i.e. "valor”, “vitality” or in J. J. Rousseau’s sense of the term amour-propre. In the evaluating and interpretive sense this notion frequently co-occurs with the notions of the sense of personal dignity, dignity and respect. The importance of “recognition” is connected with the development of economics Fukayama answers the question of aim and values in accordance with Plato saying that when a people becomes richer, more cosmopolitan and better educated it demands not only a greater richness but also the recognition of its position. The second part of the paper contains reflections on problems discussed during the meeting of the 2O'h World Congress of Philosophy held in Boston. It can be said that they concentrated on: appreciation of minority philosophy as a part of cultural pluralism; broadening of intercultural dialogue, acceptance of diversity and pluralism of truth, freedom of discussion, openness on different world views. An important issue was the guidance towards the education of people, especially the young ones, as it is helpful in solving intellectual conflicts and in shaping the intellectual integrity. The notion of paideia was referred to in this case. The task is to teach how to live a morally and intellectually independent lives. The basis is also to be the ethical education without authorities which will enable man to investigate the sense of existence and to find orientation in the world by himself or herself. This means that already from childhood it is necessary to teach generally human ethics or philosophical ethics, which will prevent an inflation of human rights.